(untitled) (Fiep Bulletin - online, 2012)
The use of anabolic androgenic steroids (AAS) has been disseminated in the gyms, and a lot of times these drugs are marketed within the academy. Thus, the physical education teachers who work in academies are prone to questions about these drugs, and may interfere with its use. The objective of this study was to analyze the knowledge of AAS by physical education teachers working in academies in Belém-PA. We used to collect data and an anonymous closed questionnaire, applied to 90 teachers. The degree of knowledge of respondents about AAS was compared according to level of education, through non-parametric statistics, X2 test (chi-square test), considering the confidence interval p <0.05. The results on substances classified as AAS for physical education teachers who work in academies, was similar to that of lay individuals users of these drugs. In relation to the same side effects seem to have enough scientific knowledge, considering that flavor, decreased spermatogenesis, increased risk of tendon tears and muscle damage were rarely reported as side effects from AAS. It is concluded that scientific knowledge of AAS analyzed by physical education teachers who work in academies of Belém, does not seem to distinguish individuals lay users of these drugs.